The effect of Rear-End collisions on triaxial acceleration to occupant cervical and lumbar Spines: An analysis of IIHS data. (September 2022) - McCleery, Caitlin H.; Limousis-Gayda, Manon; Rubio, Eloy; Sie, Matthew; Hashish, Rami
Highlights: ATD head and pelvis accelerations are greater than at the sled in rear impacts. Horizontal acceleration at the ATD head/pelvis is greater than vertical components. Differing dynamics are experienced by spinal level, with similar directional trends. Shear may be an important spinal loading mode/injury mechanism in rear-end impacts. Seat loading responses do not appear to alter occupant dynamics by vehicle type. Abstract: Rear-end impacts are the most frequent type of the more than seven million motor vehicle collisions (MVCs) occurring annually in the United States. The cervical and lumbar spine are the most commonly injured sites as a result of rear-end collisions. The direction and magnitude of accelerations and forces to the spine are considered primary indicators of injury. Yet, there is a dearth of research regarding the relation and quantification of vehicle to occupant accelerations, as well as triaxial acceleration components (and thus, forces) to occupant spines in rear-end impacts. Therefore, the current study utilizes the Insurance Institute of Highway Safety (IIHS) test database to examine the relative relations between vehicle and occupant accelerations, as well as between component accelerations experienced at the cervical and lumbar spines in rear-end collisions. Anthropometric test device (ATD) head and pelvis accelerometer data from IIHS sled testing are used as representative measures of acceleration experienced at the cervical and lumbar spine, respectively. Peak resultant acceleration is calculated at the head and pelvis, and peak directional components (x, y, and z) of acceleration are compared to resultants. This analysis revealed significantly higher occupant head than sled (2.17 ± 0.4 × Sled; p < 0.001) and pelvis than sled (1.24 ± 0.27 × Sled; p < 0.001) accelerations. There were also significant differences across triaxial acceleration components relative to resultant at the head (x = 0.99 ± 0.02, y = 0.11 ± 0.05, z = 0.34 ± 0.06; p < 0.001 for all comparisons) and pelvis (x = 0.94 ± 0.06, y = 0.12 ± 0.14, z = 0.35 ± 0.08; p < 0.001 for all comparisons). A secondary analysis examining differences in occupant dynamics by seat designs across vehicle type revealed significant differences only between the pelvis z component accelerations in the passenger vehicle and SUV groups (passenger vehicle:SUV = 1.07, p < 0.001). Due to the uniform nature of IIHS sled testing protocols, this analysis reflects similarities in seat properties rather than between vehicle types. These results may provide a simplistic approach to quantify the magnitude of directional accelerations and forces to occupant spines in rear-end collisions.